Do surveillance cameras affect unruly behavior?: a close look at grandstands - Mikael Priks (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper studies how surveillance cameras affect unruly spectator behaviour in the highest Swedish soccer league. Swedish stadiums introduced surveillance cameras at different points in time during the years 2000 and 2001. I exploit the exogenous variation that occurred due to differences across stadiums in the processing time to get permits to use cameras as well as delays in the supply of the equipment. Conditioning on stadium fixed effects, I find that the unruly behavior was approximately 65 percent lower in stadiums with cameras compared to stadiums without. The natural experiment provides a unique possibility to address problems regarding endogeneity, simultaneous policy interventions and displacement effects.
Keywords: K40; J01; 330; surveillance cameras; crime; natural experiments; Videoprodukt; Kriminalpolitik; Sport; Großveranstaltung; Kriminalität; Schweden